(untitled) (International Journal of Food and Nutritional Sciences, 2022)
A biomedical research point is the computerised analysis of white platelet tumour diseases like Leukemia and Myeloma. A patient’s health can be greatly improved by detecting problems early. In the event of a cancer discovery, blood smear images are a reliable and accurate source of information. It is imperative that feature extraction and reduction be done correctly when evaluating cancer growth finding such leukaemia cancer image. Diagnosing blood cancer manually is possible by a lumbar puncture, lymph node biopsy, and bone marrow biopsy. White blood cancer cells can be misdiagnosed and the patient’s life put at risk if they are detected manually. As a result, faster detection and fewer misdiagnoses are achieved by automatic detection. Detecting blood cancer using existing algorithms and approaches has been the focus of this paper.